Diaphragm for alkaline water electrolysis, alkaline water electrolyzer, and alkaline water electrolysis method

By using a separator composed of a porous membrane with anisotropy of gases and a porous support in alkaline water electrolysis, the problem of difficult to effectively isolate the gas in alkaline water electrolysis is solved, and the effect of improving the purity of the target generated gas is achieved.

CN119790191APending Publication Date: 2025-04-08NIPPON SHOKUBAI CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380063070.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In alkaline water electrolysis, when the oxygen produced by the anode chamber and the hydrogen produced by the cathode chamber pass through the porous membrane, it is difficult to effectively isolate, resulting in gas mixing, affecting resource utilization and safety.

Method used

An alkaline water electrolysis membrane is composed of a porous film including an organic polymer resin and inorganic particles and a porous support. The membrane realizes anisotropy of gas permeability through a specific gap formed between the porous film and the porous support through the impregnation part, thereby improving the recovery rate and purity of the target generated gas.

Benefits of technology

By utilizing gas permeability, the purity of the target generated gas in alkaline water electrolysis can be effectively improved, and resource utilization efficiency and safety can be enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790191A_ABST
    Figure CN119790191A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a separator for alkaline water electrolysis, which is capable of improving the purity of a target product gas in alkaline water electrolysis. The present invention is a separator for alkaline water electrolysis, which comprises a porous membrane containing an organic polymer resin and inorganic particles, and a porous support, an impregnated part in which the porous membrane is impregnated in the porous support; the impregnated part has a pair of main surfaces, and the impregnated part has a void having a size of 0.5-10 [mu] m between the porous membrane and the porous support; the separator for alkaline water electrolysis has a gas transmission anisotropy in which the gas transmission rate from one of the pair of main surfaces to the other main surface is different from the gas transmission rate from the other main surface to the one main surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a diaphragm for alkaline water electrolysis, an alkaline water electrolysis cell and an alkaline water electrolysis method. Background Art

[0002] In the past, in order to realize a low-carbon society, the introduction of renewable energy such as solar power generation and wind power generation has been promoted. The power generation of solar power generation, wind power generation, etc. varies due to meteorological conditions, so it is impossible to achieve a balance between the supply and demand of electricity, and surplus electricity may be generated. In recent years, a technology called power to gas (Power to Gas) that stores and utilizes such surplus electricity in the form of energy has attracted attention. The above technology is a technology that converts surplus electricity into gas fuels such as hydrogen and methane by electrolysis of water.

[0003] As a method for obtaining hydrogen gas by electrolysis of water, a common method is to apply a direct current to water to which sodium hydroxide, potassium hydroxide, etc. are added. This method is also called alkaline water electrolysis.

[0004] In alkaline water electrolysis, an alkaline water electrolyzer having an anode chamber and a cathode chamber separated by a diaphragm (diaphragm for alkaline water electrolysis) is used. Since electrolysis is carried out by the movement of electrons (or ions), the diaphragm needs to have high ion permeability in order to carry out electrolysis efficiently. In addition, gas barrier properties are also required to separate the oxygen generated in the anode chamber from the hydrogen generated in the cathode chamber. In addition, since alkaline water electrolysis uses a high-concentration alkaline aqueous solution of about 30%, or is carried out at about 80 to 90°C, the diaphragm also needs to be resistant to high temperatures and alkalis.

[0005] In order to cope with such a situation, various diaphragms for alkaline water electrolysis have been proposed so far (for example, Patent Documents 1 to 3).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-129563

[0009] Patent Document 2: Japanese Patent Application Publication No. 2017-2389

[0010] Patent Document 3: Japanese Patent Application No. 2020-527193 Summary of the invention

[0011] Problems to be solved by the invention

[0012] In addition, in alkaline water electrolysis, as described above, oxygen is produced in the anode chamber (anode) and hydrogen is produced in the cathode chamber (cathode). These two gases are separated by the diaphragm arranged between the electrodes, but because the diaphragm has a porous structure, a lot of gases are respectively passed through and mixed. From the aspect of resource utilization and safety, it is preferred to recycle these two gases with high purity. In addition, it is preferred to improve the purity of the desired gas in the generated gas according to the purpose or operating conditions after recovery.

[0013] The present invention has been made in view of the above-mentioned current situation, and an object of the present invention is to provide a diaphragm for alkaline water electrolysis that can improve the purity of a target generated gas in alkaline water electrolysis.

[0014] Means for solving problems

[0015] The inventors have conducted various studies on alkaline water electrolysis diaphragms, and found that the alkaline water electrolysis diaphragm having a porous membrane and a porous support body including an organic polymer resin and inorganic particles, an impregnation portion formed by impregnating the porous membrane in the porous support body, and a gap of a specific size between the porous membrane and the porous support body has the following gas permeation anisotropy: the gas permeability from one of a pair of main surfaces to the other main surface is different from the gas permeability from the other main surface of the pair of main surfaces to the one main surface. It is also found that in the present invention, by using the gas permeation anisotropy to set the orientation of the diaphragm in alkaline water electrolysis, the recovery rate of the target generated gas can be improved, and the desired generated gas with high purity can be obtained, thereby completing the present invention.

[0016] That is, the present invention provides the following aspects of the invention.

[0017] [1] A diaphragm for alkaline water electrolysis, comprising a porous membrane comprising an organic polymer resin and inorganic particles, and a porous support; an impregnation portion comprising the porous membrane impregnated in the porous support; and a pair of main surfaces, wherein the impregnation portion has a gap of 0.5 to 10 μm between the porous membrane and the porous support, wherein the diaphragm for alkaline water electrolysis has the following gas permeation anisotropy: the gas permeability from one of the pair of main surfaces to the other main surface is different from the gas permeability from the other main surface of the pair of main surfaces to the one main surface.

[0018] [2] A diaphragm for alkaline water electrolysis, comprising a porous membrane comprising an organic polymer resin and inorganic particles, and a porous support; an impregnation portion in which the porous membrane is impregnated in the porous support, and a non-impregnation portion in which the porous membrane is not impregnated in the porous support; and a pair of main surfaces, wherein the impregnation portion forms one of the pair of main surfaces, and the non-impregnation portion forms the other of the pair of main surfaces, and in the one main surface, the impregnation portion has a gap of 0.5 to 10 μm between the porous membrane and the porous support.

[0019] [3] The alkaline water electrolysis diaphragm according to [1] or [2] above, wherein the ratio of the void volume between the porous membrane and the porous support on the surface of the alkaline water electrolysis diaphragm is 1% to 8%.

[0020] [4] A diaphragm for alkaline water electrolysis as described in any one of [1] to [3] above, comprising a non-impregnation portion in which the porous membrane is not impregnated in the porous support, and a ratio of the thickness of the non-impregnation portion to the thickness of the impregnation portion [(thickness of the non-impregnation portion) / (thickness of the impregnation portion)] is 0.1 to 1.0.

[0021] [5] The alkaline water electrolysis separator according to any one of [1] to [4] above, wherein the organic polymer resin comprises at least one selected from the group consisting of polysulfone, polyethersulfone and polyphenylsulfone.

[0022] [6] The alkaline water electrolysis separator according to any one of [1] to [5] above, wherein the inorganic particles include at least one selected from the group consisting of zirconium oxide, titanium oxide, magnesium hydroxide and barium sulfate.

[0023] [7] The alkaline water electrolysis separator according to any one of [1] to [6] above, wherein the porous support comprises at least one resin selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide.

[0024] [8] An alkaline water electrolysis cell comprising an anode, a cathode, and the alkaline water electrolysis diaphragm according to any one of [1] to [7] disposed between the anode and the cathode.

[0025] [9] A method for alkaline water electrolysis, which is a method for alkaline water electrolysis using the alkaline water electrolysis cell described in [8] above, wherein water electrolysis is performed by changing the direction of the alkaline water electrolysis diaphragm according to the target generated gas in the generated gas on the anode side and the cathode side.

[0026] Effects of the Invention

[0027] The alkaline water electrolysis diaphragm of the present invention can improve the purity of the target generated gas. In addition, an alkaline water electrolysis cell and an alkaline water electrolysis method that can effectively improve the purity of the target generated gas can be appropriately provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram showing a cross section in a direction perpendicular to the main surface of an example of the alkaline water electrolysis separator of the present invention.

[0029] Figure 2 This is an example showing a state where line segments are drawn in an observation image of the impregnation portion of the separator acquired by SEM (1000 magnifications) when measuring the size of the gap between the porous membrane and the porous support.

[0030] Figure 3 FIG. 1 is an example of an observation image of the impregnation portion of the separator obtained by SEM (200 magnifications) when obtaining the ratio of the void amount between the porous membrane and the porous support. DETAILED DESCRIPTION

[0031] The present invention is described in detail below. It should be noted that a combination of two or more of the preferred embodiments of the present invention described below is also a preferred embodiment of the present invention. It should be noted that in this description, the numerical range represented as "X to Y" means greater than X and less than Y. For example, "0.5 to 10 μm" means greater than 0.5 μm and less than 10 μm.

[0032] 1. Diaphragm for alkaline water electrolysis

[0033] The alkaline water electrolysis diaphragm of the present invention comprises a porous film including an organic polymer resin and inorganic particles, and a porous support; an impregnation portion formed by impregnating the porous film in the porous support; and a pair of main surfaces, characterized in that the impregnation portion has a gap of 0.5 to 10 μm between the porous film and the porous support, and the alkaline water electrolysis diaphragm has the following gas permeation anisotropy: the gas permeability from one main surface of the pair of main surfaces to the other main surface is different from the gas permeability from the other main surface of the pair of main surfaces to the one main surface. Therefore, when the alkaline water electrolysis diaphragm of the present invention is used to electrolyze water, the target generated gas with high purity can be obtained by setting the orientation of the alkaline water electrolysis diaphragm of the present invention according to the gas whose purity is to be improved.

[0034] The alkaline water electrolysis diaphragm of the present invention has gas permeation anisotropy. The above-mentioned gas permeation anisotropy refers to the characteristic that the gas permeability from one of the pair of main surfaces of the above-mentioned diaphragm to the other main surface is different from the gas permeability from the above-mentioned other main surface of the above-mentioned pair of main surfaces to the above-mentioned one main surface. More specifically, it is a characteristic that the amount of hydrogen permeating the alkaline water electrolysis diaphragm per unit time changes according to the direction of the alkaline water electrolysis diaphragm, and it is also a characteristic that the amount of oxygen permeating the alkaline water electrolysis diaphragm per unit time changes according to the direction of the alkaline water electrolysis diaphragm. In this way, the gas permeability of the above-mentioned alkaline water electrolysis diaphragm changes according to the setting direction, so by changing the direction of the diaphragm according to the generated gas to be recovered, the purity of the recovered gas can be improved.

[0035] The alkaline water electrolysis diaphragm of the present invention comprises a porous membrane including an organic polymer resin and inorganic particles, and a porous support, comprises an impregnation portion in which the porous membrane is impregnated in the porous support, and has a pair of main surfaces.

[0036] The porous film is impregnated in the entire porous support, and is laminated as a portion consisting only of the porous film on one side of a pair of main surfaces of the porous support. On the other side of a pair of main surfaces of the porous support, the porous film is roughly flush with the porous support. In this way, the alkaline water electrolysis diaphragm of the present invention has an impregnation portion formed by the porous film being impregnated in the porous support, and a non-impregnation portion consisting only of the porous film in the porous support, wherein the impregnation portion forms one of the pair of main surfaces, and the non-impregnation portion forms the other of the pair of main surfaces.

[0037] The impregnation part has a gap of 0.5 to 10 μm between the porous membrane and the porous support. By making the impregnation part have a gap of the above-mentioned range between the porous membrane and the porous support, gas permeation anisotropy can be exerted. From the perspective of further improving gas permeation anisotropy, the size of the gap is preferably 1 to 8 μm, more preferably 2 to 7 μm.

[0038] Therefore, the alkaline water electrolysis diaphragm of the present invention can also be said to be the following diaphragm: it has a porous membrane containing an organic polymer resin and inorganic particles, and a porous support; it includes an impregnation portion formed by impregnating the porous membrane in the porous support, and a non-impregnation portion in which the porous membrane is not impregnated in the porous support; it has a pair of main surfaces, wherein the impregnation portion forms one of the pair of main surfaces, the non-impregnation portion forms the other of the pair of main surfaces, and in the one main surface, the impregnation portion has a gap of 0.5 to 10 μm between the porous membrane and the porous support. The alkaline water electrolysis diaphragm of the present invention has the following gas permeation anisotropy by having such a structure: the gas permeability from one of the pair of main surfaces to the other main surface is different from the gas permeability from the other of the pair of main surfaces to the one main surface.

[0039] The size of the voids between the porous membrane and the porous support can be determined by SEM (scanning electron microscope) observation. Specifically, first, any 10 points on the main surface of the alkaline water electrolysis separator consisting of the impregnation portion are used as observation areas. Figure 1 Schematic diagram of a cross section perpendicular to the main surface of an example of the alkaline water electrolysis diaphragm of the present invention is shown in FIG. Figure 1 In the embodiment, the alkaline water electrolysis diaphragm 1 has a porous film 2 and a porous support 3, an impregnation portion 4 formed by the porous film 2 being impregnated in the porous support 3, and a non-impregnation portion 5 consisting only of the porous film. In the impregnation portion 4, the above-mentioned observation area is selected. Then, in the above-mentioned observation area, an observation image of 1000 times is obtained using SEM. In the 10 obtained observation images (10 fields of view), the size of the void is measured using image analysis software (Image-Pro Premier, Media Cybernetics Company). Regarding the measurement of the size of the void, a line segment is drawn at intervals of 10 μm along the length direction of the porous support that looks like a fiber. The line segment is drawn from the surface of the porous support to the surface of the porous film perpendicularly relative to the surface of the porous support. Figure 2 , a diagram showing the above line segments drawn in a SEM observation image of one visual field is shown. Then, the length of the line segments is measured. The lengths of all line segments are measured, and their average value is used as the size of the gap in one visual field. The same process is performed in 10 visual fields, and the average value of the 10 visual fields is used as the size of the gap.

[0040] The ratio of the void volume between the porous film and the porous support on the surface of the alkaline water electrolysis diaphragm is preferably 1 to 8%. If the ratio of the void volume is within the above range, ion permeability and gas permeation anisotropy are excellent. From the perspective of further improving ion permeability and gas permeation anisotropy, the ratio of the void volume is more preferably 2 to 7%, and more preferably 2.5 to 6.5%.

[0041] The ratio of the void amount between the porous film and the porous support in the alkaline water electrolysis diaphragm can be determined by the following method. That is, any 10 points in the main surface of the alkaline water electrolysis diaphragm consisting of the impregnation portion (the main surface on the side where the non-impregnation portion is not formed) are used as the observation area. In the above-mentioned observation area, an observation image with a magnification of 200 is obtained using SEM. In the 10 observation images (10 fields of view) obtained, the ratio of the void amount is measured using image analysis software (Image-ProPremier, Media Cybernetics Company). Specifically, first, 1) in the above-mentioned observation image, the void portion and the non-void portion are visually identified (refer to Figure 3 ). 2) By placing the cursor on the gap, you can specify the brightness of the gap. 3) By placing the cursor on the non-gap ( Figure 3 4) Through the above 2) and 3), the void part and the non-void part are identified based on the specified brightness, so the area measurement processing is performed on them respectively, and the area values ​​of the void part and the non-void part and their total value are calculated. 5) The same processing of 1) to 4) is performed in 10 fields of view, and the average value of the 10 fields of view is taken as the ratio of the above void amount. It should be noted that the void observed in the observation image at 200 times is equivalent to the void between the above porous membrane and the above porous support. The void formed inside the porous membrane is very small, so it can only be observed in the observation image at about 10,000 times.

[0042] In the alkaline water electrolysis diaphragm, the ratio of the thickness of the non-impregnated portion to the thickness of the impregnated portion [(thickness of the non-impregnated portion) / (thickness of the impregnated portion)] is preferably 0.1 to 1.0. When the ratio of the thickness of the non-impregnated portion to the thickness of the impregnated portion is within the above range, the gas permeation anisotropy is excellent. From the perspective of further improving the gas permeation anisotropy, the ratio of the thickness of the non-impregnated portion to the thickness of the impregnated portion is more preferably 0.2 to 0.9, further preferably 0.3 to 0.8, and further more preferably 0.4 to 0.7.

[0043] Regarding the ratio of the thickness of the non-impregnated portion to the impregnated portion, for example, when the alkaline water electrolysis diaphragm comprises an impregnated portion in which the porous membrane is impregnated in the entire porous support, and a non-impregnated portion consisting only of the porous membrane, a digital micrometer (trade name: Coolant Proof Micrometer MDC-PXT, manufactured by Mitutoyo Co., Ltd.) can be used to measure 10 points of each of the porous support and the alkaline water electrolysis diaphragm, and the average value can be calculated to obtain the ratio. For example, Figure 1 When a porous membrane as shown is impregnated in the entire porous support, the thickness of the alkaline water electrolysis diaphragm and the thickness of the porous support can be calculated separately. Assuming that the thickness of the impregnation portion is the same as the film thickness of the porous support, the value obtained by subtracting the thickness of the impregnation portion from the film thickness of the alkaline water electrolysis diaphragm is calculated as the thickness of the non-impregnation portion.

[0044] The thickness of the alkaline water electrolysis diaphragm is not particularly limited and can be appropriately selected according to the size of the equipment used, handling properties, etc. From the perspective of the gas barrier properties, ion permeability, and strength of the diaphragm, it is preferably 50 to 1000 μm, more preferably 100 to 500 μm, and even more preferably 200 to 400 μm.

[0045] The porosity of the alkaline water electrolysis diaphragm is preferably 20 to 80% by volume, more preferably 25 to 75% by volume, and further preferably 30 to 70% by volume. If the porosity is within the above range, the electrolyte is continuously filled into the pores in the membrane, so that a membrane having excellent ion permeability and excellent gas barrier properties can be obtained. The porosity can be obtained by immersing the alkaline water electrolysis diaphragm in the electrolyte overnight and calculating the porosity based on the mass of the diaphragm before and after the absorption of the liquid. Specifically, it can be obtained by the following formula.

[0046] Porosity (volume %) = [(mass of the separator after immersion - mass of the separator before immersion) / density of the electrolyte] × 100

[0047] The porous membrane and the porous support constituting the above-mentioned separator for alkaline water electrolysis are described.

[0048] (porous membrane)

[0049] The porous membrane contains an organic polymer resin and inorganic particles.

[0050] Examples of the organic polymer resin include fluorine-based resins, olefin-based resins, and aromatic hydrocarbon-based resins.

[0051] Examples of the fluorine-based resin include ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride, polyvinyl fluoride, vinylidene fluoride-hexafluoropropylene copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers, polychlorotrifluoroethylene, and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers.

[0052] Examples of the olefin-based resin include polyethylene, polypropylene, polybutene, and polymethylpentene.

[0053] Examples of the aromatic hydrocarbon resin include polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylene sulfone, polyarylate, polyetherimide, polyimide, and polyamideimide.

[0054] From the aspects of excellent heat resistance, alkali resistance, and excellent solubility in the solvent described later, the above-mentioned organic polymer resin is preferably an aromatic hydrocarbon resin, more preferably comprises at least one selected from the group consisting of polysulfone, polyethersulfone and polyphenylsulfone, and further preferably comprises polysulfone. The above-mentioned organic polymer resin may comprise only one kind, or may comprise two or more kinds.

[0055] The content of the organic polymer resin in 100% by mass of the porous membrane is preferably 10 to 40% by mass, more preferably 15 to 35% by mass, and even more preferably 20 to 30% by mass.

[0056] Examples of the inorganic particles include metal hydroxides or metal oxides of magnesium, zirconium, titanium, zinc, aluminum, tantalum, etc.; sulfates of calcium, barium, lead, strontium, etc.; nitrides of titanium, zirconium, hafnium, etc.; carbides of titanium, zirconium, hafnium, etc. Among them, from the perspective of further improving ion permeability, metal hydroxides or metal oxides are preferred, and at least one selected from the group consisting of zirconium oxide, titanium oxide, magnesium hydroxide, and barium sulfate is more preferred, and at least one selected from the group consisting of zirconium oxide and magnesium hydroxide is further preferred. The inorganic particles may include only one kind, or may include two or more kinds.

[0057] The inorganic particles may or may not be surface treated. Examples of the surface treatment include known surface treatments using a silane coupling agent, stearic acid, oleic acid, phosphoric acid ester, and the like.

[0058] The shape of the above-mentioned inorganic particles is not particularly limited, and can be any shape such as amorphous; granular; particulate; plate-like; flaky, hexagonal plate-like or other plate-like; fibrous, among which, from the aspect of easy dispersion in a solution to prepare a coating solution, granular, plate-like, and fibrous are preferred, from the aspect of adhesion to the resin and ion permeability, granular and plate-like are more preferred, plate-like is further preferred, and flaky is particularly preferred.

[0059] The average particle size of the inorganic particles is preferably 0.01 to 1.5 μm. When the average particle size of the inorganic particles is within the above range, ion permeability and gas barrier properties are excellent. From the perspective of further improving ion permeability and gas barrier properties, the average particle size of the inorganic particles is more preferably 0.1 to 1.0 μm, and more preferably 0.2 to 0.5 μm.

[0060] The above-mentioned average particle size is the volume average particle size (D50) obtained by measuring the particle size distribution based on the laser diffraction method. Specifically, the average particle size is measured using a laser diffraction / scattering particle size distribution measuring device ("LA-950 type" manufactured by Horiba Manufacturing Co., Ltd.), and the median diameter (D50) in the particle size distribution of the volume basis is used as the average particle size. It should be noted that the inorganic particles are mixed with a 0.2% by mass sodium hexametaphosphate aqueous solution and ultrasonically irradiated to disperse it, and the dispersion is used as a measurement sample. Specifically, it can be obtained by the method described in the embodiments described later.

[0061] The aspect ratio of the inorganic particles is preferably 1.0 to 8.0. When the aspect ratio of the inorganic particles is within the above range, ion permeability and gas barrier properties are excellent. From the perspective of further improving ion permeability and gas barrier properties, the aspect ratio of the inorganic particles is more preferably 2.0 to 8.0, more preferably 2.5 to 7.0, and even more preferably 3.0 to 6.0.

[0062] In this specification, aspect ratio refers to the ratio of the longest diameter (a) to the shortest diameter (b) [(a) / (b)]. The inorganic particles are observed using SEM, and the ratio [(a) / (b)] is measured using analysis software for any 10 inorganic particles in the obtained image. The average value of the ratio [(a) / (b)] of the 10 inorganic particles is taken as the aspect ratio of the inorganic particles. The shortest particle diameter among the particle diameters orthogonal to the longest diameter is usually taken as the shortest diameter (b).

[0063] The specific surface area of ​​the inorganic particles is preferably 5 to 35 m 2 When the specific surface area of ​​the inorganic particles is within the above range, the ion permeability is excellent. The specific surface area of ​​the inorganic particles is more preferably 5.5 to 25 m 2 / g, more preferably 6 to 20 m 2The above-mentioned specific surface area can be obtained by measuring using a BET specific surface area meter, and specifically, can be obtained by the method described in the examples described later.

[0064] The content of the inorganic particles in 100% by mass of the porous membrane is preferably 60 to 95% by mass, more preferably 65 to 92% by mass, and even more preferably 75 to 90% by mass.

[0065] In the porous film, the organic polymer resin preferably contains 10 to 60 parts by mass, more preferably 15 to 55 parts by mass, and further preferably 20 to 50 parts by mass relative to 100 parts by mass of the inorganic particles. If the content ratio of the inorganic particles to the organic polymer resin is within the above range, the alkaline water electrolysis diaphragm has excellent ion permeability, gas barrier properties, heat resistance, and alkali resistance.

[0066] From the viewpoint of further improving ion permeability, gas barrier properties, and strength, the thickness of the porous film is preferably 50 to 1000 μm, more preferably 100 to 500 μm, and even more preferably 200 to 400 μm.

[0067] (Porous Support)

[0068] The porous support is porous and is a member constituting the support of the alkaline water electrolysis diaphragm. The porous support is preferably a sheet-like member.

[0069] As the material of the porous support, for example, resins such as polyethylene, polypropylene, polysulfone, polyethersulfone, polyphenylsulfone, polyphenylene sulfide, polyketone, polyimide, polyetherimide, and fluorine resin can be cited. One of them can be used alone, or two or more of them can be used in combination. Among them, from the aspect of being able to exert excellent heat resistance and alkali resistance, it is preferred to contain at least one resin selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide, and more preferably to contain at least one resin selected from the group consisting of polypropylene and polyphenylene sulfide.

[0070] The form of the porous support may be, for example, nonwoven fabric, woven fabric, net, porous membrane, or a mixed fabric of nonwoven fabric and woven fabric, preferably nonwoven fabric, woven fabric or net, more preferably nonwoven fabric and net, and further preferably nonwoven fabric.

[0071] The porous support used in the present invention is preferably a nonwoven fabric, a woven fabric or a net containing at least one resin selected from the group consisting of polypropylene, polyethylene and polyphenylene sulfide. The porous support is more preferably a nonwoven fabric or a net containing polyphenylene sulfide.

[0072] When the porous support is in sheet form, the thickness of the porous support is not particularly limited as long as the alkaline water electrolysis separator of the present invention can exert the effects of the present invention, but is preferably 30 to 2000 μm, more preferably 50 to 1000 μm, and further preferably 80 to 250 μm.

[0073] When the porous support is in sheet form, the unit mass is preferably 20 to 200 g / m 2 When the unit mass is within the above range, the ion permeability and gas barrier properties are excellent. The unit mass of the porous support is more preferably 40 to 150 g / m 2 , more preferably 60 to 100 g / m 2 .

[0074] 2. Method for manufacturing diaphragm for alkaline water electrolysis

[0075] The alkaline water electrolysis membrane of the present invention can be produced, for example, by a non-solvent induced phase separation method comprising the following steps (1) to (4).

[0076] (1) Step of preparing a porous film-forming composition

[0077] (2) A step of applying the porous film-forming composition to a porous support

[0078] (3) A step of bringing the coated porous support into contact with a non-solvent

[0079] (4) Step of drying the porous support after the contact

[0080] Each step is described below.

[0081] Step (1) is a step of preparing a porous film-forming composition. The porous film-forming composition is prepared by mixing the organic polymer resin, inorganic particles, a solvent and a nonionic surfactant. The mixing method is not particularly limited. For example, a resin solution obtained by dissolving an organic polymer resin in a solvent and a dispersion (slurry) obtained by dispersing inorganic particles in a solvent can be prepared, and then these can be mixed with a nonionic surfactant.

[0082] The solvent is not particularly limited as long as it has the property of dissolving the organic polymer resin, and examples thereof include N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, etc. These solvents may be used alone or in combination of two or more.

[0083] The content of the organic polymer resin in the resin solution is not particularly limited, but is preferably 10 to 50% by mass, more preferably 15 to 45% by mass, and even more preferably 20 to 40% by mass.

[0084] The content of the inorganic particles in the dispersion is not particularly limited, but is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and even more preferably 40 to 60% by mass.

[0085] The dispersion may further contain a dispersant in order to improve the dispersibility of the inorganic particles. Examples of the dispersant include known dispersants such as phosphoric acid polyester, polyvinyl pyrrolidone, and polyacrylic acid.

[0086] When preparing the resin solution or the dispersion or mixing them, a known apparatus such as a method using a mixer, a bead mill, a ball mill, a jet mill, a disperser, a sand mill, a roll mill, a pot mill, a paint shaker, etc. can be used.

[0087] The resin solution and the dispersion are preferably mixed such that the organic polymer resin is preferably 10 to 60 parts by mass, more preferably 15 to 55 parts by mass, and even more preferably 20 to 50 parts by mass based on 100 parts by mass of the inorganic particles.

[0088] As the above-mentioned nonionic surfactant, for example, glycerol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene alkyl ether, polyoxyalkylene derivatives, etc. can be cited. These solvents can be used alone or in combination of two or more. The porous film-forming composition contains the above-mentioned nonionic surfactant, so that water can easily diffuse into the impregnation portion in step (3). As a result, in the impregnation portion, a gap of 0.5 to 10 μm in size is easily formed between the porous film and the porous support.

[0089] The step (2) is a step of applying the porous film-forming composition obtained in the step (1) to a porous support.

[0090] The coating method is not particularly limited, and a known method such as die coating, spin coating, gravure coating, curtain coating, spraying, or a method using a coater or a coating machine can be used.

[0091] The coating amount of the porous film forming composition is not particularly limited, as long as it is an amount that allows the porous film forming composition to be impregnated in the entire porous support. For example, in the case of using a sheet-like porous support, the porous film forming composition is preferably applied to one side surface of the porous support and is infiltrated until it penetrates into the other side surface of the porous support.

[0092] Step (3) is a step of contacting the porous support after applying the porous film forming composition in the above step (2) with a non-solvent. By contacting the porous support after the above application with a non-solvent, the non-solvent diffuses into the porous film forming composition applied, and the organic polymer resin insoluble in the non-solvent solidifies. On the other hand, the solvent in the porous film forming composition soluble in the non-solvent dissolves. By producing such phase separation, the organic polymer resin solidifies to form a film (porous film) containing inorganic particles and having holes.

[0093] Examples of a method for bringing the porous support into contact with a non-solvent include a method of immersing the porous support in the non-solvent (coagulation bath) and the like.

[0094] The non-solvent is not particularly limited as long as it has the property of not substantially dissolving the organic polymer resin, and examples thereof include water (ion exchange water); lower alcohols such as methanol, ethanol, propanol, or mixed solvents thereof, among which water is preferred from the perspective of economy and drainage treatment. In addition, the non-solvent may contain a small amount of the same solvent as that contained in the coating film in addition to the above components.

[0095] From the aspect of easily forming a gap of the above-mentioned size between the above-mentioned porous membrane and the above-mentioned porous support, the above-mentioned porous support is preferably in contact with the non-solvent as soon as possible after the above-mentioned coating. If the time before the contact with the non-solvent after the above-mentioned coating is long, the coating surface will solidify before contact with the non-solvent, and the non-solvent is not easy to penetrate, and it may be difficult to form a porous membrane with a desired structure. The period before contact with the non-solvent after the above-mentioned coating is preferably less than 20 seconds. Thus, in the impregnation portion, a gap of 0.5 to 10 μm in size is easily formed between the porous membrane and the porous support.

[0096] Step (4) is a step of drying the porous support after contacting with the non-solvent in the above step (3). By drying the coating film solidified in the above step (3) and removing the non-solvent, a porous membrane can be formed.

[0097] The drying is not particularly limited and can be performed by a known method. The drying temperature is preferably 60 to 150° C., more preferably 70 to 140° C. The drying time is preferably 0.5 to 120 minutes, more preferably 1 to 60 minutes, and even more preferably 1 to 30 minutes.

[0098] Thus, the alkaline water electrolysis diaphragm of the present invention can be produced simply through the above steps (1) to (4).

[0099] 3. Alkaline water electrolyzer

[0100] An alkaline water electrolyzer having an anode, a cathode, and the alkaline water electrolysis diaphragm disposed between the anode and the cathode is also one of the present invention. In the alkaline water electrolyzer, the side where the anode exists is the anode chamber, and the side where the cathode exists is the cathode chamber, separated by the alkaline water electrolysis diaphragm. When the alkaline water is electrolyzed, oxygen is generated on the anode side (anode chamber). In addition, hydrogen is generated on the cathode side (cathode chamber).

[0101] Examples of the anode and cathode include known electrodes formed of a conductive substrate containing nickel, a nickel alloy, or the like.

[0102] The alkaline water electrolysis diaphragm of the present invention has gas permeation anisotropy, so by changing the orientation of the above-mentioned alkaline water electrolysis diaphragm according to the target generated gas to perform water decomposition, the purity of the target generated gas can be improved. For example, in the case where one main surface of the above-mentioned alkaline water electrolysis diaphragm is composed of an impregnation portion formed by the above-mentioned porous membrane infiltrating the above-mentioned porous support, and the other main surface is composed of a non-impregnation portion, if the diaphragm is arranged in a manner such that the main surface composed of the impregnation portion is oriented toward the anode side to perform water electrolysis, the permeation of oxygen from the anode side to the cathode side can be suppressed, so the purity of the hydrogen produced at the cathode can be improved. In addition, if the diaphragm is arranged in a manner such that the main surface composed of the impregnation portion is oriented toward the cathode side to perform water electrolysis, the permeation of hydrogen from the cathode side to the anode side can be suppressed, so the purity of the oxygen produced at the anode can be improved.

[0103] 4. Alkaline water electrolysis method

[0104] An alkaline water electrolysis method using an alkaline water electrolysis cell having an alkaline water electrolysis diaphragm of the present invention is also one of the present invention. The alkaline water electrolysis cell comprises an anode, a cathode, and an alkaline water electrolysis diaphragm disposed between the anode and the cathode. The alkaline water electrolysis diaphragm comprises a porous membrane comprising an organic polymer resin and inorganic particles, and a porous support, an impregnation portion comprising the porous membrane impregnated in the porous support, and has a pair of main surfaces. The impregnation portion has a gap of 0.5 to 10 μm between the porous membrane and the porous support. The alkaline water electrolysis diaphragm has the following gas permeation anisotropy: the gas permeability from one of the pair of main surfaces to the other main surface is different from the gas permeability from the other main surface of the pair of main surfaces to the one main surface. Using such an alkaline water electrolysis cell, alkaline water electrolysis is performed by changing the orientation of the alkaline water electrolysis diaphragm according to the target produced gas among the produced gases on the anode side and the cathode side.

[0105] The method for electrolyzing alkaline water of the present invention is not particularly limited, and can be performed by a known method. For example, the alkaline water electrolysis tank can be filled with an electrolyte solution and an electric current can be applied to the electrolyte solution.

[0106] As the above-mentioned electrolyte, an alkaline aqueous solution in which an electrolyte such as potassium hydroxide or sodium hydroxide is dissolved is used. The concentration of the electrolyte in the above-mentioned electrolyte is not particularly limited, but is preferably 20 to 40% by mass from the aspect of further improving the electrolysis efficiency. In addition, as the temperature during electrolysis, from the aspect of further improving the ion conductivity of the electrolyte and further improving the electrolysis efficiency, it is preferably 50 to 120° C., and more preferably 80 to 90° C.

[0107] The current application conditions can be carried out using known conditions and methods, and the current application is usually 0.2 A / cm 2 Above, preferably 0.3A / cm 2 Above. If the applied current density is high, more hydrogen and oxygen can be obtained in a short time, so hydrogen can be produced efficiently. However, when the current density is too high, the generated hydrogen and oxygen adhere to the ion permeable membrane or electrode to inhibit the reaction, or the overvoltage increases due to the electrode reaction resistance, so the electrolysis voltage increases, the electric energy required for electrolysis increases, and the electrolysis efficiency deteriorates. Therefore, it is preferred to adjust the electrolysis voltage to about 2V, for example, within the range of not more than 1.5 to 2.5V, so as to increase the current density.

[0108] Example

[0109] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0110] In the present examples, the measurement conditions of various physical properties and the like are as follows.

[0111] <Average Particle Size of Inorganic Particles>

[0112] The inorganic particles (powder) are mixed with a 0.2 mass % sodium hexametaphosphate aqueous solution and dispersed using an ultrasonic cleaner. For the obtained inorganic particle dispersion, a laser diffraction / scattering particle size distribution measuring apparatus (trade name: LA-950, manufactured by Horiba, Ltd.) is used to adjust the red laser transmittance to 90-98% and the blue laser transmittance to 85-92%, and the particle size distribution is measured. The median diameter (d50) in the obtained volume-based particle size distribution is taken as the average particle size (μm) of the inorganic particles.

[0113] <Specific surface area of ​​inorganic particles>

[0114] The specific surface area of ​​the inorganic particles is measured using a BET surface area meter (trade name: Macsorb HM model-1210, manufactured by Mountech). Specifically, 1 g of inorganic particles (powder) as a measurement sample is placed in a sample cell, and degassing is performed at 200°C while nitrogen gas is passed into the sample cell. After the degassing treatment, the sample cell is immersed in liquid nitrogen while nitrogen gas is passed into the sample cell, and nitrogen is adsorbed on the measurement sample at a temperature of -196°C. Next, the sample cell is maintained at room temperature, and the amount of nitrogen released is measured, thereby determining the specific surface area based on the BET method. Three measurements are performed for each sample, and the average value is taken as the specific surface area (m 2 / g).

[0115] <Aspect Ratio of Inorganic Particles>

[0116] For inorganic particles (powders), an observation image with a magnification of 20,000 times was obtained using FE-SEM (trade name: JSM-7600F, manufactured by JEOL Ltd.). For any 10 particles in the obtained image, the ratio a / b of the longest diameter a to the shortest diameter b of each particle was measured using analysis software (trade name: Image-Pro Premier, Media Cybernetics), and the average value of these ratios was calculated as the aspect ratio of the inorganic particles.

[0117] <Film thickness>

[0118] The thickness of the porous support and the obtained alkaline water electrolysis diaphragm was measured using a digital micrometer (trade name: Coolant Proof Micrometer MDC-PXT, manufactured by Mitutoyo). Any 10 points were measured and the average value was used as the film thickness. The thickness of the impregnation portion of the alkaline water electrolysis diaphragm was set to be the same as the film thickness of the porous support, and the value obtained by subtracting the thickness of the impregnation portion from the film thickness of the diaphragm after infiltration was calculated and used as the thickness of the non-impregnation portion.

[0119] <Gap size between porous membrane and porous support>

[0120] In the main surface of the obtained alkaline water electrolysis diaphragm where the non-impregnation portion is not formed, an observation image (magnification: 1,000 times) measured based on FE-SEM (trade name: JSM-7600F, manufactured by Japan Electronics Co., Ltd.) is obtained in any 10 fields of view. For the obtained observation image, analysis software (trade name: Image-Pro Premier, MediaCybernetics Company) is used to identify the porous membrane, porous support, and void. Afterwards, along the surface of the porous support observed as a fibrous porous support, a line segment perpendicular to the surface of the porous support is drawn from the porous support to the surface of the porous membrane at intervals of 10 μm. The length of all line segments is measured, and their average value is used as the void size between the porous support and the porous membrane in one field of view. The same treatment is performed on the remaining 9 fields of view, and the average value of 10 fields of view is used as the void size between the porous support and the porous membrane.

[0121] <Void ratio between the porous film on the separator surface and the porous support>

[0122] In the main surface of the non-impregnation part not formed in the 2 main surfaces of the obtained alkaline water electrolysis diaphragm, the observed image (magnification: 200 times) measured based on FE-SEM (trade name: JSM-7600F, manufactured by NEPCO) is obtained in any 10 visual fields. For the obtained surface observation image, analysis software (trade name: manufactured by Image-Pro Premier, Media Cybernetics) is used for analysis. First, 5 points are respectively specified to be the brightness of the part judged as the void and the part judged as the porous film by the identification of the analyst. Afterwards, the part matching with the specified brightness is extracted by the processing of the analysis software, and the area of ​​the void region is automatically calculated, and the ratio relative to the total area of ​​the observation visual field is calculated as the ratio of the void amount in 1 visual field. The remaining 9 visual fields are subjected to the same treatment, and the average value of 10 visual fields is used as the ratio of the void amount between the porous support and the porous film.

[0123] <Evaluation of alkaline water electrolysis>

[0124] In an alkaline water electrolysis cell having the following tank structure and under the following electrolysis conditions, an alkaline water electrolysis test was performed using an alkaline water electrolysis diaphragm, and gas purity was measured to measure the permeation of hydrogen and oxygen. Specifically, the gas purity of the anode chamber and the cathode chamber was measured under the condition that the impregnation portion of the diaphragm was oriented toward the anode electrode (orientation condition A), and then the gas purity was measured under the condition that the impregnation portion of the diaphragm was oriented toward the cathode electrode (orientation condition B). The method for measuring gas purity is described below.

[0125] ·Cell structure and electrolysis conditions

[0126] The composition of the slot elements is: electrode area 27.8cm 2 Anode (Ni mesh substrate coated with Ni-Co oxide) and cathode (Ni mesh substrate coated with Ru-Ln oxide), current collector, end plate, chamber block, joint. The anode and cathode are zero-pole-gap structures that are pressed on the diaphragm for alkaline water electrolysis by the spring structure of the current collector. During electrolysis, a 30 mass % potassium hydroxide aqueous solution is circulated at 20 mL / min in both the anode and cathode. At this time, the anolyte and cathode liquid are circulated and supplied in completely different systems, so that the two liquids will not mix in the reservoir and piping system. The temperature is 80°C at both the anode and cathode, and the piping outlet is open to atmospheric pressure. After gas-liquid separation, a water bridge is set between the anode-cathode piping to form a structure in which the anode and cathode are at the same pressure. The electrolysis conditions are from 1.0 to 0.2 Acm -2 At 0.2Acm -2 The constant current density is applied at intervals. The waiting time at each constant current density is 1.0Acm -2 2 hours, at 0.8Acm -2 3 hours, at 0.6Acm -2 4 hours at 0.4Acm -2 5 hours, at 0.2Acm -2 The gas purity was measured by gas chromatography for 8 hours, immediately after the waiting time, and every 30 minutes, and this was repeated 4 to 5 times until the gas purity value stabilized.

[0127] <Gas Purity>

[0128] The alkaline water electrolyzer provided with the obtained alkaline water electrolysis diaphragm was measured for the purity of oxygen at the anode and the purity of hydrogen at the cathode, which were the generated gases during alkaline water electrolysis. Specifically, in order to remove water vapor from the gas obtained from the electrolyzer outlet piping through the gas-liquid separator, the gas was passed through a water removal piping system cooled at 0 to 1°C, and then the purity of oxygen and hydrogen was measured using a gas chromatograph (trade name: GC-2014A, manufactured by Shimadzu Corporation).

[0129] [Example 1]

[0130] <Preparation of Inorganic Particle Dispersion>

[0131] Magnesium hydroxide particles (plate-shaped, average particle size 0.36 μm, specific surface area: 10 m 2 / g, aspect ratio 4.7) 100 parts by mass, N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation) 60 parts by mass, and 3 parts by mass of phosphoric acid polyester were mixed and dispersed in a bead mill using zirconium oxide beads for 30 minutes. The zirconium oxide beads were then removed to obtain a magnesium hydroxide particle dispersion.

[0132] <Preparation of Porous Film-Forming Composition>

[0133] 200 parts by mass of the obtained magnesium hydroxide particle dispersion, 100 parts by mass of a polysulfone resin solution prepared by dissolving a polysulfone resin (trade name: Ultrason S3010, manufactured by BASF) at a concentration of 35% by mass in N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), and 1 part by mass of sorbitan monooleate were mixed using a rotary revolution mixer (trade name: Awatori Rentaro ARE-500, manufactured by Thinky Co., Ltd.) at room temperature for 1000 min. -1 The mixture was mixed at a rotation speed of 100 for 10 minutes and then filtered through a SUS mesh to obtain a porous film-forming composition.

[0134] <Formation of Separator>

[0135] In a nonwoven fabric composed of polyphenylene sulfide fibers (basis weight: 100 g / m 2 The porous film-forming composition (coating amount: 28 mg / cm 2 ), the porous film-forming composition is impregnated in the nonwoven fabric until it penetrates the surface of the other side. After 15 seconds of coating, the nonwoven fabric impregnated with the porous film-forming composition is immersed in a water tank and water bathed at room temperature for 3 minutes to obtain a water-containing film composed of magnesium hydroxide particles, polysulfone resin and nonwoven fabric. The obtained film is dried at 80°C for 30 minutes using a dryer to obtain an alkaline water electrolysis diaphragm. The obtained alkaline water electrolysis diaphragm has a film thickness of 260μm, a thickness of 70μm in the non-impregnation portion, and a thickness of 190μm in the impregnation portion. The gap size between the porous film of the diaphragm and the nonwoven fabric is 2.6μm, and the ratio of the gap amount is 2%.

[0136] <Evaluation of alkaline water electrolysis>

[0137] Under orientation condition A, 1000mA / cm 2 The oxygen concentration in the cathode chamber at the current density was 0.00 vol%, and the hydrogen concentration in the anode chamber was 0.12 vol%. Under the orientation condition B, the oxygen concentration in the cathode chamber at the same current density was 0.21 vol%, and the hydrogen concentration in the anode chamber was 0.02 vol%.

[0138] [Example 2]

[0139] <Preparation of Inorganic Particle Dispersion>

[0140] Barium sulfate particles (plate-shaped, average particle size 0.90 μm, specific surface area: 5 m 2 / g, aspect ratio 5.2) 200 parts by mass, N,N-dimethylacetamide (manufactured by Mitsubishi Gas Chemical Co., Ltd.) 150 parts by mass, and polyvinyl pyrrolidone 5 parts by mass were mixed and dispersed in a bead mill using zirconium oxide beads for 30 minutes. The zirconium oxide beads were then removed to obtain a barium sulfate particle dispersion.

[0141] <Preparation of Porous Film-Forming Composition>

[0142] 200 parts by mass of the obtained barium sulfate particle dispersion, 100 parts by mass of a polyethersulfone resin solution prepared by dissolving a polyethersulfone resin (trade name: Ultrason E3010, manufactured by BASF) at a concentration of 35% by mass in N,N-dimethylacetamide (manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 2 parts by mass of sorbitan monooleate were mixed using a rotary revolution mixer (trade name: Awatori Rentaro ARE-500, manufactured by Thinky Co., Ltd.) at room temperature for 1000 min. -1 The mixture was mixed at a rotation speed of 100 for about 10 minutes and then filtered through a SUS mesh to obtain a porous film-forming composition.

[0143] <Formation of Separator>

[0144] In a nonwoven fabric composed of polyphenylene sulfide fibers (basis weight: 60 g / m 2 The porous film-forming composition (coating amount: 20 mg / cm 2 ), the porous film forming composition is impregnated in the non-woven fabric until it penetrates the surface of the other side. After 10 seconds of coating, the non-woven fabric impregnated with the porous film forming composition is immersed in a water tank and water bathed at room temperature for 3 minutes to obtain a water-containing film composed of barium sulfate particles, polyethersulfone resin and non-woven fabric. The obtained film is dried at 80°C for 30 minutes using a dryer to obtain an alkaline water electrolysis diaphragm. The obtained alkaline water electrolysis diaphragm has a film thickness of 145μm, a thickness of the non-impregnated portion of 15μm, a thickness of the impregnated portion of 130μm, a gap size between the porous film of the diaphragm and the non-woven fabric of 0.6μm, and a gap ratio of 1%.

[0145] <Evaluation of alkaline water electrolysis>

[0146] Under alignment condition A, the oxygen concentration in the cathode chamber was 0.01 vol%, and the hydrogen concentration in the anode chamber was 0.08 vol%. Under alignment condition B, the oxygen concentration in the cathode chamber was 0.13 vol%, and the hydrogen concentration in the anode chamber was 0.02 vol%.

[0147] [Example 3]

[0148] <Preparation of Inorganic Particle Dispersion>

[0149] Zirconia particles (spherical, average particle size 0.02 μm, specific surface area: 25 m 2 / g, aspect ratio 1.1), 200 parts by mass of N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), 150 parts by mass of N-methyl-2-pyrrolidone, and 5 parts by mass of polyacrylic acid were mixed and dispersed in a bead mill using zirconia beads for 30 minutes. The zirconia beads were then removed to obtain a zirconia particle dispersion.

[0150] <Preparation of Porous Film-Forming Composition>

[0151] 200 parts by mass of the obtained zirconium oxide particle dispersion, 100 parts by mass of a polyphenylsulfone resin solution prepared by dissolving a polyphenylsulfone resin (trade name: Ultrason P3010, manufactured by BASF) at a concentration of 35% by mass in N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), and 5 parts by mass of sorbitan monolaurate were mixed using a rotary revolution mixer (trade name: Awatori Rentaro ARE-500, manufactured by Thinky Co., Ltd.) at room temperature for 1000 min. -1 The mixture was mixed at a rotation speed of 100 for about 10 minutes and then filtered through a SUS mesh to obtain a porous film-forming composition.

[0152] <Formation of Separator>

[0153] In a non-woven fabric composed of polypropylene fibers (basis weight: 80g / m 2 The porous film-forming composition (coating amount: 76 mg / cm 2 ), the porous film forming composition is impregnated in the nonwoven fabric until it penetrates the surface of the other side. After 20 seconds of coating, the nonwoven fabric impregnated with the porous film forming composition is immersed in a water tank and water bathed at room temperature for 3 minutes, thereby solidifying the coated film to obtain a water-containing film. The obtained film is dried at 80°C for 30 minutes using a dryer to obtain an alkaline water electrolysis diaphragm. The obtained alkaline water electrolysis diaphragm has a film thickness of 310μm, a thickness of the non-impregnated portion of 150μm, a thickness of the impregnated portion of 160μm, a gap size between the porous film of the diaphragm and the nonwoven fabric of 9.5μm, and a gap ratio of 8%.

[0154] <Evaluation of alkaline water electrolysis>

[0155] Under alignment condition A, the oxygen concentration in the cathode chamber was 0.03 vol%, and the hydrogen concentration in the anode chamber was 0.24 vol%. Under alignment condition B, the oxygen concentration in the cathode chamber was 0.28 vol%, and the hydrogen concentration in the anode chamber was 0.03 vol%.

[0156] [Example 4]

[0157] <Preparation of Inorganic Particle Dispersion>

[0158] Zirconia particles (spherical, average particle size 0.36 μm, specific surface area: 10 m 2 / g, aspect ratio 1.1), 200 parts by mass of N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), 150 parts by mass of N-methyl-2-pyrrolidone, and 6 parts by mass of phosphoric acid polyester were mixed and dispersed in a bead mill using zirconium oxide beads for 30 minutes. The zirconium oxide beads were then removed to obtain a zirconium oxide particle dispersion.

[0159] <Preparation of Porous Film-Forming Composition>

[0160] 200 parts by mass of the obtained zirconium oxide particle dispersion, 100 parts by mass of a polysulfone resin solution prepared by dissolving a polysulfone resin (trade name: Ultrason S3010, manufactured by BASF) at a concentration of 35% by mass in N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), and 5 parts by mass of sorbitan monolaurate were mixed using a rotary revolution mixer (trade name: Awatori Rentaro ARE-500, manufactured by Thinky) at room temperature for 1000 min. -1 The mixture was mixed at a rotation speed of 100 for about 10 minutes and then filtered through a SUS mesh to obtain a porous film-forming composition.

[0161] <Formation of Separator>

[0162] In a nonwoven fabric composed of polyphenylene sulfide fibers (basis weight: 100 g / m 2 The porous film-forming composition (coating amount: 45 mg / cm 2), the porous film forming composition is impregnated in the nonwoven fabric until it penetrates the surface of the other side. After 20 seconds of coating, the nonwoven fabric impregnated with the porous film forming composition is immersed in a water tank and water bathed at room temperature for 3 minutes, thereby solidifying the coated film to obtain a water-containing film. The obtained film is dried at 80°C for 30 minutes using a dryer to obtain an alkaline water electrolysis diaphragm. The obtained alkaline water electrolysis diaphragm has a film thickness of 260μm, a thickness of 70μm in the non-impregnation portion, a thickness of 190μm in the impregnation portion, a gap size of 2.4μm between the porous film of the diaphragm and the nonwoven fabric, and a gap ratio of 2%.

[0163] <Evaluation of alkaline water electrolysis>

[0164] Under alignment condition A, the oxygen concentration in the cathode chamber was 0.02 vol%, and the hydrogen concentration in the anode chamber was 0.25 vol%. Under alignment condition B, the oxygen concentration in the cathode chamber was 0.25 vol%, and the hydrogen concentration in the anode chamber was 0.04 vol%.

[0165] [Comparative Example 1]

[0166] <Preparation of Inorganic Particle Dispersion>

[0167] Zirconia particles (spherical, average particle size 0.02 μm, specific surface area: 25 m 2 / g, aspect ratio 1.1), 200 parts by mass of N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation), 100 parts by mass of N-methyl-2-pyrrolidone, and 2 parts by mass of polyvinyl pyrrolidone were mixed and dispersed in a bead mill using zirconia beads for 30 minutes. The zirconia beads were then removed to obtain a zirconia particle dispersion.

[0168] <Preparation of Porous Film-Forming Composition>

[0169] 200 parts by mass of the obtained zirconium oxide particle dispersion and 100 parts by mass of a polysulfone resin solution prepared by dissolving a polysulfone resin (trade name: Ultrason S3010, manufactured by BASF) at a concentration of 35% by mass in N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation) were mixed using an auto-revolution mixer (trade name: Awatori Rentaro ARE-500, manufactured by Thinky) at room temperature for 1000 min. -1 The mixture was mixed at a rotation speed of 100 for about 10 minutes and then filtered through a SUS mesh to obtain a porous film-forming composition.

[0170] <Formation of Separator>

[0171] In a nonwoven fabric composed of polyphenylene sulfide fibers (basis weight: 100 g / m 2The porous film-forming composition (coating amount: 59 mg / cm 2 ), the porous film forming composition is impregnated in the nonwoven fabric until it penetrates the surface of the other side. After 60 seconds of coating, the nonwoven fabric impregnated with the porous film forming composition is immersed in a water tank and water bathed at room temperature for 3 minutes, thereby solidifying the coated film to obtain a water-containing film. The obtained film is dried at 80°C for 30 minutes using a dryer to obtain an alkaline water electrolysis diaphragm. The obtained alkaline water electrolysis diaphragm has a film thickness of 240μm, a thickness of the non-impregnated portion of 150μm, a thickness of the impregnated portion of 90μm, a gap size of 0.2μm between the porous film of the diaphragm and the nonwoven fabric, and a gap ratio of 0.5%.

[0172] <Evaluation of alkaline water electrolysis>

[0173] Under alignment condition A, the oxygen concentration in the cathode chamber was 0.21 vol%, and the hydrogen concentration in the anode chamber was 0.22 vol%. Under alignment condition B, the oxygen concentration in the cathode chamber was 0.25 vol%, and the hydrogen concentration in the anode chamber was 0.20 vol%.

[0174] Therefore, when water electrolysis is performed using the alkaline water electrolysis diaphragm of the embodiment, the concentration of the generated oxygen or hydrogen changes depending on the orientation conditions, so it can be confirmed that the alkaline water electrolysis diaphragm of the embodiment has gas permeation anisotropy, and it can be seen that by changing the orientation of the diaphragm, the purity of the target generated gas can be improved.

[0175] Explanation of symbols

[0176] 1 Diaphragm for alkaline water electrolysis

[0177] 2 porous membrane

[0178] 3. Porous support

[0179] 4 Impregnation

[0180] 5 Non-impregnated area

[0181] 6. Gap

[0182] 7 Line segments

Claims

1. A diaphragm for alkaline water electrolysis, comprising a porous membrane comprising an organic polymer resin and inorganic particles, and a porous support; comprising an impregnation portion formed by impregnating the porous membrane into the porous support; having a pair of main surfaces, wherein: The impregnation part has a gap of 0.5 μm to 10 μm between the porous membrane and the porous support. The alkaline water electrolysis membrane has gas permeation anisotropy in which a gas permeability from one of the pair of main surfaces to the other main surface is different from a gas permeability from the other main surface to the one main surface.

2. A diaphragm for alkaline water electrolysis, comprising a porous membrane comprising an organic polymer resin and inorganic particles, and a porous support; comprising an impregnation portion in which the porous membrane is impregnated in the porous support, and a non-impregnation portion in which the porous membrane is not impregnated in the porous support; having a pair of main surfaces, wherein: The impregnation portion forms one of the pair of main surfaces, The non-impregnation portion forms the other of the pair of main surfaces, In the one main surface, the impregnation portion has a gap having a size of 0.5 μm to 10 μm between the porous membrane and the porous support.

3. The alkaline water electrolysis diaphragm according to claim 1 or 2, wherein: On the surface of the alkaline water electrolysis separator, the ratio of the void volume between the porous membrane and the porous support is 1% to 8%.

4. The alkaline water electrolysis diaphragm according to any one of claims 1 to 3, wherein comprising a non-impregnated portion in which the porous membrane is not impregnated into the porous support, The ratio of the thickness of the non-impregnated portion to the thickness of the impregnated portion, ie, (thickness of the non-impregnated portion) / (thickness of the impregnated portion) is 0.1 to 1.

0.

5. The alkaline water electrolysis diaphragm according to any one of claims 1 to 4, wherein The organic polymer resin includes at least one selected from the group consisting of polysulfone, polyethersulfone and polyphenylsulfone.

6. The alkaline water electrolysis diaphragm according to any one of claims 1 to 5, wherein The inorganic particles include at least one selected from the group consisting of zirconium oxide, titanium oxide, magnesium hydroxide, and barium sulfate.

7. The alkaline water electrolysis diaphragm according to any one of claims 1 to 6, wherein The porous support includes at least one resin selected from the group consisting of polypropylene, polyethylene, and polyphenylene sulfide. 8 . An alkaline water electrolysis cell comprising an anode, a cathode, and the alkaline water electrolysis diaphragm according to claim 1 , which is arranged between the anode and the cathode.

9. An alkaline water electrolysis method using the alkaline water electrolysis cell according to claim 8, wherein: Water electrolysis is performed by changing the orientation of the alkaline water electrolysis diaphragm according to the target produced gas among the produced gases on the anode side and the cathode side.

Citation Information

Patent Citations

  • Diaphragm for electrolyzing alkaline water and method for manufacturing the same

    JP2014129563A

  • Diaphragm for alkaline water electrolysis and method for producing the same

    JP2017002389A

  • Alkaline hydrolysis-strengthened separator

    JP2020527193A